The startup checklist : 25 steps to a scalable, high-growth business - Rose, David S., 1957- (Online access with DDA: Askews (Economics), 2016)
"25 Steps to Found and Scale a High-Growth Business The Startup Checklist is the entrepreneur's essential companion. While most entrepreneurship books focus on strategy, this invaluable guide provides the concrete steps that will get your new business off to a strong start. You'll learn the ins and outs of startup execution, management, legal issues, and practical processes throughout the launch and growth phases, and how to avoid the critical missteps that threaten the foundation of your business. Instead of simply referring you to experts, this discussion shows you exactly which experts you need, what exactly you need them to do, and which tools you will use to support them & mdash;and you'll gain enough insight to ask smart questions that help you get your money's worth. If you're ready to do big things, this book has you covered from the first business card to the eventual exit. Over two thirds of startups are built on creaky foundations, and over two thirds of startup costs go directly toward cleaning up legal and practical problems caused by an incomplete or improper start. This book helps you sidestep the messy and expensive clean up process by giving you the specific actions you need to take right from the very beginning. Understand the critical intricacies of legally incorporating and running a startup Learn which experts you need, and what exactly you need from them Make more intelligent decisions independent of your advisors Avoid the challenges that threaten to derail great young companies The typical American startup costs over $30,000 and requires working with over two dozen professionals and service providers before it even opens for business & mdash;and the process is so complex that few founders do it correctly. Their startups errors often go unnoticed until the founder tries to seek outside capital, at which point they can cost thousands of dollars to fix. or even completely derail an investment. The Startup Checklist helps you avoid these problems and lay a strong foundation, so you can focus on building your business"--